Analysis Of Subgrade Repair Using Lime By Modeling In The Field For Design Of The Foundation Foundation Of The Rigid Pavement Micro Pole - Moch. Fajar Rahmadhoni; Agus Tugas Sudjianto; Aji Suraji; Muhamad Cakrawala (CV. Creative Tugu Pena, 2026)
The subgrade is an important component in the road pavement structure because it functions as the main lining of the traffic load. However, the condition of the land on Jl. North Baruk III, Kedung Baruk, Surabaya, tends to be less stable because it is dominated by soil types such as soft sauce, plastic clay, and loose -grained soils that have low carrying capacity. This study aims to evaluate subgrade improvement using chemical stabilization methods with a mixture of dolomite lime of 6%, as well as analyzing its impact on the value of density, CBR, and carrying capacity of micro pole foundations. The method used is laboratory experiments and field modeling. The results showed that the addition of lime 6% increased the value of soil density from 95.84% to 99.70% (an increase of 4.03%), the CBR value from 2.53% to 4.09% (an increase of 61.66%), and the carrying capacity of the foundation of micro pole from 27.84 kN to 38.66 KN (increased 38.87%). Thus, the combination of lime stabilization and the utilization of micro pole effectively increases the carrying capacity and stability of the subgrade to support the rigid pavement construction.